Penerapan Komunitas yang Inklusif di Kelompok Sel Mahasiswa Rantau di Bandung - Ferry Simanjuntak; Priskila Elizabeth; Natal Riang Daeli; Marlen Vera Hattu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Education becomes a very important aspect for every individual to obtain broader knowledge. One way to achieve a better education is to continue your studies to college. The environment in which individuals interact with others has a great influence on student behavior. Especially for overseas students, the challenges faced are more due to the distance that separates parents and families. Therefore, the establishment of a cell group community for overseas students in Bandung has great potential to form an inclusive environment that will continue to grow over time. In an inclusive environment, students can learn to appreciate cultural diversity and broaden their understanding of the world. Moreover, cell groups can also be a source of support in their studies, careers, and personal lives, helping students feel more connected and secure in a new environment. Therefore, the establishment of cell groups is an important first step in building an inclusive and sustainable community in Bandung. To understand more, our team tries to prepare the needs of overseas students.